The sustainable development of Hi-Tech human resources under the background of excessive real estate investment - Wu, Qian; Liu, Yuehan; Li, Weiyi (Edelweiss Applied Science and Technology, 2025)
The development level of high-tech industries serves as a primary indicator of urban core competitiveness, with talent agglomeration being a critical factor. Promoting synergy between talent and industries is essential for the transformation and upgrading of resource-based cities. Currently, China's high-tech sector accounts for a relatively low proportion of the national economy amid structural imbalances, and overheated real estate investment may exert profound negative effects on talent agglomeration. Based on panel data from 256 Chinese cities, this study employs spatial econometric models to analyze these relationships. The findings reveal that excessive real estate investment and secondary industry agglomeration significantly inhibit the agglomeration of high-tech talents, consistently observed across both developed and non-first-tier cities. The mechanism underlying this relationship is that while real estate investment stimulates the agglomeration of secondary industries, the latter crowds out human and other critical resources required by high-tech industries, resulting in a significant negative correlation between the two. This study provides important insights for promoting talent agglomeration and fostering sustainable urban development.